Theory of Behaviour dalam Virtual Interactivity untuk Meningkatkan Purchase Intention - Kurniawati; Yolanda Masnita; Latifah Al Khasbi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
With the growing evolution of social media, influencers have become an important intermediary between influencers and their audiences through the content they create, which can increase the role of social media as a marketing tool. The beauty industry faces challenges such as buyer disappointment after purchasing ']bnvc products reviewed by influencers, and the existence of influencers who accept endorsements of inauthentic products, causing losses to companies with genuine products and also deceiving their audiences by becoming a marketing medium for inauthentic products. Positive perceptions of the attractiveness of celebrity influencers have the potential to influence purchase intention. This research uses PSB Theory to analyze factors such as celebrity influencer's credibility, celebrity influencer attractiveness, attitude, virtual interactivity, brand awareness, and brand loyalty. It is hoped that the results of this research can become a basis for maximizing purchase intention through the factors of celebrity influencer's credibility, celebrity influencer attractiveness, attitude, virtual interactivity, brand awareness and brand loyalty